The visual opportunity spaces of oil: in promotion, protest, and warning. Issue 5 (20th October 2022) - Widener, Patricia
Abstract : This essay illustrates how petroleum, the oil industry, and oil corporations manifest and are manifested across publicly visible and accessible platforms, or visual opportunity spaces, in promotion, conflict, consumption, and warning. The product, industry operations, and brand name corporations are represented as essential entities, benevolent neighbours, educators, or entertainment providers; as problematic or disruptive; or as hazardous. Yet when comparing everyday observations, corporate-sponsored images of goodwill are not equally countered by images of resistance or government-mandated public health warnings. Positive images blanket public opportunity spaces in ways that lead to the normalisation of the industry's presence and of the consumption and production of petroleum, while critical or cautious visual narratives are minimised to sporadic or event-based protest activities or minuscule and routinised warnings. A comparative analysis sheds light on the imbalance of visual indicators of promotion, criticism, and vigilance. Oil corporations or the industry dominate and are permitted to dominate access to visual spaces in volume, duration, and positive or gratifying sensations that are not equally countered by civil society's challenges or concerns, or by notices of climate change or human or ecological health risks.